2013
DOI: 10.1136/jfprhc-2013-100605
|View full text |Cite
|
Sign up to set email alerts
|

Changing convention in combination oral contraceptives: estradiol and nomegestrol acetate in a monophasic 24/4 regimen

Abstract: Initial oral contraceptive regimens were characterised by high doses of ethinylestradiol (EE) and a progestogen in a 21-day regimen that either included seven additional hormone-free tablets or simply the 21 days of combination hormonal tablets. These regimens were developed to ensure high contraceptive effectiveness, regular and predictable withdrawal bleeding episodes to mimic a menstrual cycle, and minimal unscheduled vaginal bleeding. However, these regimens were associated with adverse tolerability and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“… 3 , 4 Over the past few decades, the EE dose has been reduced to improve the safety and risk profiles. More recently, COCs with natural estrogen derivatives, estradiol or estradiol valerate, have been developed, 5 , 6 with the prospect of decreasing cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Over the past few decades, the EE dose has been reduced to improve the safety and risk profiles. More recently, COCs with natural estrogen derivatives, estradiol or estradiol valerate, have been developed, 5 , 6 with the prospect of decreasing cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%
“…It is postulated that combined oral contraceptives (COCs) containing synthetic estradiol, which is structurally identical to endogenous oestrogen,3 are potentially safer and better tolerated than those containing ethinylestradiol, the synthetic oestrogen most commonly used in COCs 4. The progestogen in Zoely is nomegestrol acetate, which is structurally related to progesterone,5 in contrast to the majority of progestogens in COCs that are derived from 19-nortestosterone6 and associated with androgenic effects 7. It is suggested that nomegestrol acetate, with its greater specificity for progesterone receptors, may minimise the potential for androgenic, oestrogenic and glucocorticoid effects 7.…”
mentioning
confidence: 99%
“…The introduction of oral contraceptives in the 1960s represents one of the significant advances in women's health, impacting women and society from a medical, social and political viewpoint. While, the overall health benefits of contraception and oral contraception have been well documented [3,4,5]. The oral contraceptive pill (OCP) provides very effective reversible contraception/ and has an excellent overall safety and tolerability profile.…”
Section: Introductionmentioning
confidence: 99%